Design of cooling structure improvement of hybrid commutated converter valve - Xu He; Lu Qu; Xiaoguang Wei; Fang Cai; Zhanqing Yu; Tianhui Yang; Yurong Luo; Gongyi Zhang (High Voltage)
Abstract This paper presents a thermal management framework for 120 kV hybrid commutated converter (HCC) valves, addressing critical cooling challenges in multi‐hundred‐MW power conversion systems. Power loss calculations under rated (1.0 p.u.) and overload (1.2 p.u.) conditions demonstrate that HCC valves achieve comparable loss levels to line commutated converter counterparts while enabling active turn‐off control. Comparative analysis of radiator configurations identifies 2‐parallel branch connections as optimal. Integrated thermal‐fluid models combining 3D finite element analysis and computational fluid dynamics reveal significant temperature gradients and flow maldistribution in baseline designs. On this basis, this paper modifies the flow from equal flow resistance allocation to heat‐based allocation and it reduces maximum integrated gate‐commutated thyristor temperature rise by 7.3% at 1.2 p.u. with minimal pressure drop variation. Experimental validation confirms the proposed cooling strategy enhances valve safety margins through improved heat dissipation balance, providing a validated theoretical foundation for high‐power converter thermal design.